Cloud Cost Optimization Methodologies for Cloud Migrations - Srinivasa Rao Thumala (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Cloud migration has become a strategic necessity for organizations looking to leverage the scalability, flexibility, and performance of cloud computing. However, one of the critical challenges during this transition is optimizing costs to achieve a balance between performance and budget. This research explores methodologies for cloud cost optimization, focusing on managing compute, storage, and network resources effectively across different cloud providers. The study combines technical insights, cost optimization strategies, and emerging trends, providing actionable recommendations for organizations.